Eccentric free muscular perforator flaps in the proximal lateral leg for hand and foot reconstruction. Issue 8 (7th October 2021) - Yen, Yu‐Hsiu; Lo, Shih‐Lun; Liu, Shih‐Pi; Pu, Chi‐Ming
Abstract: Background: We aimed to introduce our modifications by using eccentrically located muscular perforators to shorten the distance between the recipient vessels and the flap pedicle for overcoming the "short pedicle" drawback of the proximal lateral leg perforator (PLLP) flap. Patients and methods: A retrospective review of 12 cases undergoing free PLLP flap for hand and foot regions reconstruction during 2010 and 2019. The mean age was 43.3 years. Most defects resulted from burn and trauma injuries. The dimensions of defects ranged from 8 × 1.5 cm 2 to 12 × 6.5 cm 2 . Muscular perforators were designed eccentrically 1–3 cm away from the central point of the flap to shorten the distance between the recipient vessels and the pedicle. The flap was designed to be 0.5–1 cm larger than the defect. Results: The flap size ranged from 9 × 2 cm 2 to 15 × 6 cm 2 . All pedicles were long enough to ensure an appropriate anastomosis without tension. The post‐operative course in all cases was uneventful. All flaps survived without complications. Primary repair of the donor sites was performed in all patients. Donor leg function was not hampered by flap harvesting. All patients were satisfied with the scar after at least 1 year of follow‐up. Conclusion: Based on our experience, selection of the eccentric locations of the musculo‐cutaneous perforators were effective methods to overcome the short pedicle length of this flap type. Using our modifications, thin PLLP flaps can be used in foot and hand reconstruction with minimal donor site morbidity and a high success rate.